Ordinances of Jersey City, Passed By The Board Of Aldermen since May 1, 1871, under the Act Entitled "An Act to Re-organize the Local Government of Jersey City," Passed March 31, 1871, and the Supplements Thereto, pg. 41, Ordinances of Jersey City, NJ, In Relation to the Sidewalks, Public Grounds and Streets in Jersey City, § 26 (1874). - (:unkn) unknown (General Publisher, 1874)
No person shall, within this city, fire or discharge any gun, pistol, cannon, or fowling piece or other fire-arms, unless in defense of his property or person
--
Keywords: DISCHARGE